Persepsi Masyarakat Tentang Instagram PPID Kota Semarang - Pradana, Ilham Ananda; Hidayat, Muhammad Noor (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Instagram is a photo-sharing application that allows users to take pictures, apply digital filters, and share them through various social networking services, including Instagram. Semarang City has an Instagram account, PPID (Information and Documentation Management Officer), which provides information about activities in the city of Semarang. This study uses the theory of mass communication and perception. The method used in this study is qualitative with a descriptive approach. Data collection techniques include interviews and observations. Data analysis techniques consist of data reduction, data presentation, and conclusion. The results showed that the Semarang City PPID account helped the community access information that occurred in Semarang, such as official information from the government, natural disaster warnings, entertainment events, regional assistance, and others. Most people are enthusiastic about the Semarang City PPID Instagram account because it helps them know the information needed.